The Development Research: Assessment Instruments of Science Literacy Based on Minimum Competency Assessment (AKM) Level 4th for Solar System Concepts - Alfi Salamah; TjiptoTjipto Prastowo; Eko Hariyono (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
The literacy competence of students is getting lower. The Ministry of National Education issues literacy in schools regulations and develops literacy assessment formats to improve it. It continues to experience improvements because it can still not boost student achievement. AKM is the latest student literacy competency assessment policy. Considering that the program is new and will be carried out next year, the number of question bank on AKM books is still limited. However, a design guide document for the development of the AKM test was launched. Therefore, good quality literacy tests are still needed. This development research aims to produce a valid and reliable AKM-based test package for the Solar System’s Reading Science Information Literacy level IV concept. And then, at the survey stage, respondents worked on the test package in the e-learning format. The test’s scoring will be used to describe the student literacy competency profile per the design guidelines for developing AKM questions. The results indicate that: (1) the AKM tests package that has been compiled is valid and reliable; (2) only 41 out of 181 students accessed the survey; (3) their highest achievements are the sufficient category, while the less category is most dominant; (4) the description is that their competence is only at the level of finding information, sub-competencies: accessing and searching for information in the text; search and select relevant information. The highest competence is understanding, sub-competence: comprehending text literally; explaining the main idea and some supporting ideas in the information text. It is competence at level 2 on the AKM test, the ability of students in grades 3 - 4 elementary school.